Solvothermally Synthesized Nickel Doped Tin Dioxide based Thick Films for H2 and NH3Gas Sensing. (2020) - Rane, Sapana S.; Shinde, Manish D.; Arbuj, Sudhir S.; Joshi, Neha; Rane, Sunit B.; Gosavi, Suresh W.
Abstract: Economical fabrication of semiconductor nanomaterials based gas sensor operating at relatively low temperature is very essential. Herein, nanostructured Nix Sn1-x O2 (where x = 0, 0.01, 0.05 and 0.1) powders were synthesized using facile solvothermal method at 200 °C for 24h. These powders were characterized using various analytical techniques viz. X-ray diffractometry, scanning electron microscopy, field emission transmission electron microscopy to understand their physico-chemical properties. Thick film pastes were formulated for the synthesized nanopowders. The thick films were printed on to glass substrates and fired at 400 C for 1h. The gas sensing performance of the resultant thick films was studied for hydrogen and ammonia. Thick film gas sensor based on Ni0.01 Sn0.99 O2 nano powder exhibited highest responseto hydrogen gas at lowest operating temperature (78 °C). On the other hand, the highest response to ammonia gas at lowest operating temperature (74 °C) was obtained in case of thick film gas sensor fabricated using nano powder of Ni0.1 Sn0.90 O2